Clinical Features of Essential Tremor in Children - Arpita Lakhotia (Pediatric Neurology Briefs Publishers, 2018)
Investigators from Cleveland Clinic Child Neurology Center reported the clinical features of essential tremor (ET) in the pediatric population.